Pengecualian Dividen Sebagai Objek Pajak Penghasilan Dalam Undang-Undang Cipta Kerja: Perhitungan Potensi Dampaknya Terhadap Penerimaan Negara - Cahyo Adi Prayogo; Imam Muhasan (Politeknik Keuangan Negara STAN, 2022)
According to Law Number 11 of 2021 concerning Job Creation, since November 2nd of 2021, dividend is excluded as an object of Income Tax. As a logical consequence, the exclusion of dividends as an object of PPh has the potential decrease in state revenue. This research is aimed to measure the potential impact of the dividend exclusion as an object of income tax on state revenue. This research is a qualitative research, with a simulation approach. From the research conducted, it is known that in the short term, the exclusion of dividends as an income tax object has the potential to cause a decrease in state revenues. However, in the long run, it can have an impact on increasing state revenues, due to increasing investment in Indonesia.